Recontextualizing Jihad in Digital Da'wah: A Corpus-Assisted Critical Discourse Analysis of NU Online - Hilmi, Mustofa; Pimay, Awaludin (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examine how the meaning of jihad is recontextualized in NU Online discourse using the Corpus-Assisted Discourse Studies (CADS) approach and Teun A. van Dijk’s Critical Discourse Analysis (CDA) model. This study uses a mixed method that integrates corpus-based quantitative analysis and CDA-based qualitative analysis. Data were obtained from 95 NU Online articles containing the keyword “jihad,” totaling 51,523 tokens, collected via Octoparse crawling and analyzed with AntConc. Collocation and concordance analysis were used to identify patterns of semantic association. In contrast, CDA was used to interpret the discourse construction of jihad at the text, social cognition, and social context levels. The results show that jihad in NU Online is situated within a positive, constructive discourse. The twelve words with the highest frequency of collocation with jihad are Resolution, NU, Meaning, Fatwa, Sabilillah, Physical, Economic, Hawa, Physical, Spiritual, Ashghar, and Akbarul. Eight words are categorized as positive, two words are neutral, and one word has a negative lexical connotation but is limited discursively. Jihad is predominantly framed as a historical response to colonialism, a normative decision by scholars, a social struggle, economic empowerment, and a moral and spiritual struggle. Physical jihad is positioned as a contextual historical phenomenon that is irrelevant in the contemporary peaceful situation. These findings confirm NU Online’s role as an important discursive actor in shaping public understanding of jihad as a moderate religious movement.